The frontostriatal subtype of mild cognitive impairment in Parkinson's disease, but not the posterior cortical one, is associated with specific EEG alterations. (August 2022) - Betrouni, Nacim; Devignes, Quentin; Bayot, Madli; Derambure, Philippe; Defebvre, Luc; Leentjens, Albert FG.; Delval, Arnaud; Dujardin, Kathy
Abstract: Background: The 'dual syndrome' hypothesis states that two cognitive subtypes can be distinguished in mild cognitive impairment in Parkinson's disease (PD-MCI): a frontostriatal one, characterized by attentional and/or executive deficits, and a posterior cortical one, characterized by visuospatial, memory and/or language deficits. The latter type has been associated with a higher risk of earlier development of PD dementia. The functional bases of these subtypes remain partly unknown. Objective: To identify EEG modifications associated with PD-MCI subtypes. Methods: 75 non-demented PD patients underwent a comprehensive neuropsychological assessment and a high-density EEG. They were classified as having normal cognition (PD-NC; n  = 37), PD-MCI with a frontostriatal subtype (PD-FS; n  = 11) or PD-MCI with a posterior cortical subtype (PD-PC; n  = 27). Two EEG analyses were performed: (a) spectral powers quantification and (b) functional connectivity analysis. Results: PD-FS patients displayed spectral and functional EEG alterations, namely (a) higher powers in the theta and delta bands, (b) lower powers in the beta2 band and (c) lower functional connectivity in the beta2 band compared to PD-NC and PD-PC patients. These alterations were mainly located in the frontal, limbic and parietal regions. There were no significant differences between PD-NC and PD-PC. Conclusion: EEG alterations previously reported in PD-MCI may only concern the frontostriatal subtype, and not the posterior-cortical subtype. This provides evidence for the dual syndrome hypothesis and emphasizes the importance of identifying PD-MCI subtypes. It also shows the promising potential of EEG to discriminate between PD-MCI subtypes.